The global loss of floristic uniqueness - Yang, Qiang; Weigelt, Patrick; Fristoe, Trevor S; Zhang, Zhijie; Kreft, Holger; Stein, Anke; Seebens, Hanno; Dawson, Wayne; Essl, Franz; König, Christian; Lenzner, Bernd; Pergl, Jan; et al. (Nature communications, 2021)
Regional species assemblages have been shaped by colonization, speciation and extinction over millions of years. Humans have altered biogeography by introducing species to new ranges. However, an analysis of how strongly naturalized plant species (i.e. alien plants that have established self-sustaining populations) affect the taxonomic and phylogenetic uniqueness of regional floras globally is still missing. Here, we present such an analysis with data from native and naturalized alien floras in 658 regions around the world. We find strong taxonomic and phylogenetic floristic homogenization overall, and that the natural decline in floristic similarity with increasing geographic distance is weakened by naturalized species. Floristic homogenization increases with climatic similarity, which emphasizes the importance of climate matching in plant naturalization. Moreover, floristic homogenization is greater between regions with current or past administrative relationships, indicating that being part of the same country as well as historical colonial ties facilitate floristic exchange, most likely due to more intensive trade and transport between such regions. Our findings show that naturalization of alien plants threatens taxonomic and phylogenetic uniqueness of regional floras globally. Unless more effective biosecurity measures are implemented, it is likely that with ongoing globalization, even the most distant regions will lose their floristic uniqueness.
Keywords: rostliny; Phylogeny; Plants; Climate; biodiverzita; zavlečené druhy; Introduced Species; fylogeneze; podnebí; Ecosystem; ekosystém; Biodiversity